Pengaruh Metode Pembelajaran Picture And Picture untuk Meningkatkan Keaktifan Belajar Siswa Pada Pembelajaran Tematik Kelas III SD Negeri 0507 Pasar Latong - Nurhalimah Harahap; Era Mutiah (STIKes Ibnu Sina Ajibarang, 2023)
The aim of this research is to determine the effect of the picture and picture learning method to increase student learning activity in thematic learning. The research method used is an experimental research method, based on this type of research data in the form of quantitative research. The data collection techniques used by researchers are tests (pretest and posttest), observation and documentation. The population of this study was taken from class III at SD Negeri 0507 Pasar Latong and the sample in this study was taken from all 33 class III students. From the results of the